Yi-Shen-Hua-Shi granule ameliorates diabetic kidney disease by the “gut-kidney axis” - Han, Cong; Shen, Zhen; Cui, Tao; Ai, Shan-shan; Gao, Ran-ran; Liu, Yao; Sui, Gui-yuan; Hu, Hong-zhen; Li, Wei (Journal of ethnopharmacology, 2023)
Yi-Shen-Hua-Shi (YSHS) granule is an effective prescription widely used in traditional Chinese medicine to treat diabetic kidney disease (DKD), its exact efficacy in treating DKD has been confirmed but the underlying regulatory mechanism has not been fully elucidated. To explore the mechanism by which YSHS granule regulates intestinal flora and serum metabolites and then regulates renal mRNA expression through the “gut-kidney axis”, so as to improve DKD. 40 rats were divided into five groups: Normal group (N) (normal saline), model group (M) (STZ + normal saline), YSHS granule low-dose group (YL) (STZ + 2.27 g kg−1 d−1), YSHS granule high-dose group (YH) (STZ + 5.54g kg−1 d−1) and valsartan group (V) (STZ + 7.38mg kg−1 d−1). After 6 weeks, changes in blood glucose, blood lipids, and renal function related indexes were observed, as well as pathological changes in the kidney and colon. Intestinal microbiota was sequenced by 16S rDNA, serum differential metabolites were identified by LC-MS/MS, and renal differences in mRNA expression were observed by RNA-seq. Further, through the association analysis of intestinal differential microbiota, serum differential metabolites and kidney differential mRNAs, the target flora, target metabolites and target genes of YSHS granule were screened and verified, and the “gut-metabolism-transcription” co-expression network was constructed. In group M, blood glucose, blood lipid and proteinuria were increased, inflammation, oxidative stress and renal function were aggravated, with the proliferation of mesangial matrix, vacuolar degeneration of renal tubules, accumulation of collagen and lipid, and increased intestinal permeability, and YSHS granule and valsartan improved these disorders to varying degrees. High dose of YSHS granule improved the diversity and abundance of flora, decreased the F/B value, greatly increased the abundance of Lactobacillus and Lactobacillus_murinus, and decreased the abundance of Prevoella UCG_001. 14 target metabolites of YSHS granule were identified, which were mainly enriched in 20 KEGG pathways, such as Glycerophospholipid metabolism, Sphingolipid metabolism and Phenylalanine, tyrosine and tryptophan biosynthesis. 96 target mRNAs of YSHS granule were also identified. The enriched top 20 pathways were closely related to glucose and lipid metabolism, of which a total of 21 differential mRNAs were expressed. Further correlation analysis revealed that Lactobacillus, Lactobacillus_murinus and Prevotella UCG_001 were highly correlated with Glycerophospholipid metabolism, Sphingolipid metabolism and Phenylalanine, tyrosine and tryptophan biosynthesis pathways. At the same time, 6 pathways including Glycerophospholipid metabolism, Arachidonic acid metabolism, Purine metabolism, Primary bile acid biosynthesis, Ascorbate and aldarate metabolism and Galactose metabolism were co-enriched by the target metabolites and the target mRNAs of YSHS granule, including 7 differential metabolites such as phosphatidylethanolamine and 7 differential genes such as Adcy3. The 7 differential metabolites had high predictive value of AUC, and the validation of 7 differential genes were highly consistent with the sequencing results. YSHS granule could improve DKD through the “gut-kidney axis”. Lactobacillus and Lactobacillus_murinus were the main driving forces. 6 pathways related to glucose and lipid metabolism, especially Glycerophospholipid metabolism, may be an important follow-up response and regulatory mechanism. [Display omitted] •Yi-Shen-Hua-Shi granule protected diabetic kidney disease by “gut-kidney axis”.•Probiotics such as Lactobacillus and Lactobacillus_murinus were the primary driving factors.•6 pathways, especially Glycerophospholipid metabolism, may be an important follow-up response and regulatory mechanism.